Fatty Infiltration of Skeletal Muscle: Mechanisms and Comparisons with Bone Marrow Adiposity - Hamrick, Mark W.; McGee-Lawrence, Meghan E.; Frechette, Danielle M. (Frontiers in Endocrinology, 2016)
Skeletal muscle and bone share common embryological origins from mesodermal cell populations and also display common growth trajectories early in life. Moreover, muscle and bone are both mechanoresponsive tissues, and the mass and strength of both tissues decline with age. The decline in muscle and bone strength that occurs with aging is accompanied in both cases by an accumulation of adipose tissue. In bone, adipocyte accumulation occurs in the marrow cavities of long bones and is known to increase with estrogen deficiency, mechanical unloading, and exposure to glucocorticoids. The factors leading to accumulation of intra- and intermuscular fat are less well understood, but recent evidence indicates that increases in intramuscular fat are associated with disuse, altered leptin signaling, sex steroid deficiency, and glucocorticoid treatment—factors that are also implicated in bone marrow adipogenesis. Importantly, accumulation of adipocytes in skeletal muscle and accumulation of intramyocellular lipid are linked to loss of muscle strength, reduced insulin sensitivity, and increased mortality among the elderly. Resistance exercise and whole-body vibration can prevent fatty infiltration in skeletal muscle and also improve muscle strength. Therapeutic strategies to prevent myosteatosis may improve muscle function and reduce fall risk in the elderly, potentially impacting the incidence of bone fracture.